2022
DOI: 10.3390/ijerph192113800
|View full text |Cite
|
Sign up to set email alerts
|

Air Quality Dispersion Modelling to Evaluate CIPP Installation Styrene Emissions

Abstract: Cured-in-place pipe (CIPP) is one of the most popular in situ rehabilitation techniques to repair sewer and water pipes. While there are multiple approaches to curing CIPP, steam-curing of styrene-based resins has been found to be associated with air-borne chemical emissions. Health officials, utilities and industry representatives have recognized the need to know more about these emissions, especially styrene. Such concern has led to multiple studies investigating the concentrations of volatile organic compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Polymerization reactions in the resin are initiated by using heat or by ultraviolet light. 2 The most popular and least expensive curing approach involves blowing steam through the uncured resin tube and out an exhaust pipe into the air. 3 Until 2017, emissions from this operation were reported to only contain a small amount of gas-phase volatile organic compound (VOC) styrene near 3 ppmv.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymerization reactions in the resin are initiated by using heat or by ultraviolet light. 2 The most popular and least expensive curing approach involves blowing steam through the uncured resin tube and out an exhaust pipe into the air. 3 Until 2017, emissions from this operation were reported to only contain a small amount of gas-phase volatile organic compound (VOC) styrene near 3 ppmv.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Additional work found styrene levels were diluted in the ambient air, as suggested by dispersion model analysis. 2,7 However, eld measurements showed that very complex and highly dynamic mixtures of multi-component chemical pollutants are in fact emitted into the atmospheric environment around the installation sites. 4,8,9 Although the chronic effects from occupational exposure require additional scrutiny, 10 acute environmental impacts of the chemicals and particulates in the emission plume have been associated with air pollution and human toxicity.…”
Section: Introductionmentioning
confidence: 99%